Realization of Spanish consonants by Polish immigrants in Granada. Contrastive study - Sosinski, Marcin (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This article analyses the phonetic characteristics of Polish immigrants residing in Granada for more than 10 years in their pronunciation of consonants. The research has been carried out on the basis of surveys collected in the non-bilingual adult Poles who have been living in Spain for at least 10 years. The work presents the description and the phonetic and acoustic comparison of the consonants that are considered the most problematic (using the PRAAT program). The contribution describes the different ways of consonantal realization in Spanish by Polish immigrants. The results demonstrate the degree of their phonetic assimilation in specific contexts. Likewise, the levels of adjustment and fit with native consonantal pronunciation are detailed. It is concluded that the factors that determine the studied phenomena are the L1 transfer, the normative pressure and the influence of orthography.